Effect of Lead in Elastomeric Bearings for Structures Located in Seismic Region. (2016) - Govardhan,; Paul, D.K.
Abstract: Seismic base isolation is one of the most commonly implemented and established earthquake protection systems. Seismic base isolation is a technique that mitigates the effects of an earthquake by essentially isolating the structure and its contents from potentially severe ground motion, especially in the frequency range where the building is most affected. Having designed seismic isolation system, the next step was to explore the fabrication of Laminated Lead Rubber Bearings (LLRB). It should be affordable and suitable for high seismic zones. Because isolators are subject to extreme deformations and loads during major earthquakes, most design codes require they be tested to demonstrate conformance with design expectations. At some point in time isolator devices may be required to be removed and replaced. One reason for this may be that the isolators get damaged during a severe earthquake. Testing can be performed to verify design properties of the isolation system over a time period. Regardless of the reasoning, isolators must be able to be accessed and removed. There may be significant time and costs associated with a structure whose isolation system is not readily and easily accessible. In this paper, an indigenous effort to develop the bearings and testing of Laminated Rubber Bearings (LRB) with and without lead core has been presented.